2017
DOI: 10.1097/tp.0000000000001267
|View full text |Cite
|
Sign up to set email alerts
|

Prolonged Survival of Pig Skin on Baboons After Administration of Pig Cells Expressing Human CD47

Abstract: Background Successful xenotransplantation will likely depend, in part, on the induction of immunological tolerance, since the high levels of immunosuppression otherwise required would likely have unacceptable side effects. Rapid clearance of administered porcine hematopoietic stem cells by primate macrophages has hampered previous attempts to induce tolerance through mixed hematopoietic chimerism across a pig-to-primate barrier. Phagocytosis is normally inhibited by binding of cell surface protein CD47 to macr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
67
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 86 publications
(70 citation statements)
references
References 33 publications
3
67
0
Order By: Relevance
“…80 Encouragingly, such prolongation has been associated with markedly prolonged donor swine skin xenografts. 81 …”
Section: The Future Of Transplantation Is Xenotransplantation and Itmentioning
confidence: 99%
“…80 Encouragingly, such prolongation has been associated with markedly prolonged donor swine skin xenografts. 81 …”
Section: The Future Of Transplantation Is Xenotransplantation and Itmentioning
confidence: 99%
“…Skin grafts on both baboons that received HSC from 18286 showed markedly prolonged survivals (70 and >23 days, respectively), while skin grafts on both baboons that received HSC from 18289 showed no difference in survival from the control baboon (14 days). These results therefore indicate a strong correlation between hCD47 expression, prolonged peripheral porcine chimerism, and marked prolongation of porcine skin grafts in the absence of concurrent immunosuppression(62). .…”
Section: Tolerance-inducing Strategies Across Xenogeneic Immunolomentioning
confidence: 81%
“…In order to test the ability of human CD47 (hCD47) to similarly improve engraftment of porcine cells in baboons, transgenic swine were produced on the GalT-KO inbred miniature swine background (62). Two swine expressing markedly different levels of the hCD47 transgene on peripheral blood mononuclear cells were produced, one expressing high levels (18286) and one expressing very low levels (18289).…”
Section: Tolerance-inducing Strategies Across Xenogeneic Immunolomentioning
confidence: 99%
See 1 more Smart Citation
“…Tena et al demonstrated that pig cells expressing human CD47 are associated with an immune-modulating effect, which leads to markedly-prolonged survival of pig skin grafts in NHPs [60]. …”
Section: Introductionmentioning
confidence: 99%